N-{4-[(5-Methylisoxazol-3-yl)sulfamoyl]phenyl}benzamide - Sumera Yasmeen; Shahzad Murtaza; Mehmet Akkurt; Islam Ullah Khan; Shahzad Sharif (Acta Crystallographica Section E, 2010)
In the title compound, C17H15N3O4S, the five-membered isoxazole ring makes dihedral angles of 80.5 (2) and 81.3 (2)° with the two benzene rings, which form a dihedral angle of 39.81 (18)° with each other. A short intramolecular C—H...O contact occurs. The crystal structure is stabilized by intermolecular N—H...O hydrogen bonds, which generate [001] chains, and further consolidated by weak C—H...O interactions.